(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study explores the intersection of consumer psychology, branding, and market adaptation within the context of globalized marketing. It argues that cultural diversity remains a critical determinant of marketing effectiveness despite increasing economic integration and digital interconnectedness. Using a conceptual research design, the article synthesizes insights from international marketing, consumer behavior, and branding literature to develop an integrative framework. The framework positions consumer psychology as a mediating mechanism that connects cultural values with brand perception, while market adaptation functions as a moderating factor that enables firms to balance global consistency with local responsiveness. The findings emphasize that consumer responses are strongly shaped by cultural orientations such as collectivism, individualism, and material values, which influence persuasion and brand trust. Branding emerges not only as a signal of quality but also as a symbolic construct negotiated within cultural contexts, often shaped by country-of-origin effects and identity-based interpretations. Adaptation is presented as a dynamic strategy rather than a binary choice, allowing firms to integrate global aspirations with cultural authenticity. The study contributes theoretically by unifying fragmented perspectives and practically by offering guidance for managers seeking to design culturally resonant strategies in diverse markets.